MANAJEMEN KRISIS DINAS KOMINFO KABUPATEN KEBUMEN BERKAITAN DENGAN PEMBERITAAN KEBUMEN SEBAGAI KABUPATEN TERMISKIN DI JAWA TENGAH - Silviana, Resy; Naryoso, Agus; Noor Rakhmad, Wiwid (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
This study examines the response of the Kebumen District Communication and Information Office (Dinas Kominfo) to media reports regarding the status of Kebumen District as the poorest district in Central Java in early 2023. The study uses a qualitative approach with descriptive methods and applies the Situational Crisis Communication Theory and Image Repair Theory. Data collection techniques include documentation studies and interviews. The results show that the Kebumen District Communication and Information Office conducted crisis management in three stages: pre-crisis, crisis response, and post-crisis. In the precrisis stage, the Dinas Kominfo monitored the media to identify issues and potential crises. They then wrote monitoring reports including recommendations for addressing the issues, but lacked standard operating procedures, teams, or crisis management training. Furthermore, in the crisis response stage, the Dinas Kominfo focused on dominating positive news and collaborated with local media, although they did not hold press conferences or issue press releases. In the post-crisis stage, the Dinas Kominfo sought to repair reputation by emphasizing positive news, engaging in two-way communication with the public, and organizing public events to divert attention from the poverty crisis. It was found that there were no specific indicators to evaluate the success of the crisis management conducted in the post-crisis stage. The statements made by the Dinas Kominfo regarding the situation tended to fall into the